Mediastinal tumor with basophilia terminating in acute leukemia - Hiçsönmez, Gönül; Göğüş, Safiye; Önder, Kürşat; Jama, Hasan; Özsoylu, Şinasi (The Turkish Journal of Pediatrics, 1987)
Prominent basophilia at the time of diagnosis of leukemia has very rarely been reported in children. Therefore, a case of marked basophilia during diagnosis of mediastinal tumor, terminating in acute leukemia, is reported. Immature basophils and basophilic granules in some leukemic cells were present in the peripheral smear and bone marrow of our patient. Postmortem examination revealed these granules containing cells in various organs infiltrated with leukemic cells in the thymus, as well as in the mediastinal mass. These granules stained metachromatically with toluidine blue but failed to stain with myeloperoxidase, Sudan black B and periodic acid-Schiff. Although the exact origin and type of leukemia could not be determined, these distinctive clinical and morphological findings in our case indicate a grave prognosis in this very rare type of clinical entity.
Keywords: acute leukemia; basophilia; mediastinal tumor; childhood